LEXICAL UNITS REPRESENTING MANIFESTATIONS OF NATIONAL SPORTS (TAMADDUN NURI JURNALI, 2024)
In this article, the lexical units representing the National People’s Games in the form of national sports are analyzed from the semantic point of view, and their types and uniqueness are studied according to the motive of naming.